(untitled) (Baghdad Science Journal, 2025)
The aim of study to evaluated cinnamic acid and its activity on complete blood count(RBC,WBC,HG,HCV,MCH,MCHC and Plat.)and removed the cytoxan damage which caused bone marrow failure and leukemia and other that due to linked the cytoxan in 7- nitrogen of guanine based of DNA that lead to dead cells. Two concentration from pure cinnamic acid (5.6, 2.8 mg ? mice weight) in first step to choice the perfect concentration in comparison with each negative control ,positive control of cytoxan and the comparison group represent vitamin C. The second step to understand cinnamic acid mechanism activity towards cytoxan by used pre- cytoxan and post – cytoxan in interaction with perfect concentration of cinnamic acid dose (2.8 mg ? mice weight).The analysis showed that cinnamic acid removed each kinds of anemia ,leukemia, bone marrow failure, hypoxia, cancer chemotherapy, hemolytic anemia and hormone erythropoietin from kidney failure in post-cytoxan than pre-cytoxan perfectly ,therefore, cinnamic acid has cure ability and removed cytoxan damage and can give to patient whom used cytoxan in transplanting body part surgeries to a void refused the part for 6 days after transplanting surgeries.